Methodological Issues of Distance Learning Organization in Universities - Khachatryan, Nonna (Bulletin of Yerevan University G: Economics, 2021)
Organizing of distance education in universities, in contrast to traditional education, uses not only technical, but also methodological additional functions. In particular, the control and motivational functions of management are changing, which is especially noticeable in the online education system. In addition, in the case of distance learning, a component of joint beneficiary management is used, when the emphasis is on student self-organization, and also student-oriented learning.
Keywords: online learning; distance learning management; educational programs; learning outcomes; MOODLE platform